KONSTRUKSI SEJARAH PERJUANGAN DAN PEMIKIRAN K.H. HASYIM ASY’ARI - Isbandiyah Isbandiyah; Pargito Pargito; Iskandar Syah (Faculty of Teacher Training and Education, University of Lampung, 2013)
The objective of this research is to understand constructions of history of K.H. Hasyim Asy’ari struggle and thinking. This research used qualitative method and literary study approach. The results showed that the construction of the history of K.H. Hasyim Asy’ari’s struggle and thinking combined the concepts of nationalism and religion to struggle for Indonesian freedom. K.H. Hasyim Asy’ari deserved a title of religious nationalist struggler because his struggle was accommodative without abandoning principles al-Qur’an and Hadits. The construction about his thinking emphasized the improvement of moral and virtues by conducting all Islamic tenets according to al-Qur’an and Hadits. His educational thinking related to the essence of Islamic education and the method of Islamic education emphasizing on the virtue of education and etiquette; the etiquette of learners and educator to achieve the expected education.Keywords: K.H. Hasyim Asy’ari, struggle, thinking